Internal Migration Challenges: The Dynamics of Rapid Population Shift from Regions to Baku in Azerbaijan - Guseynova, Gunel (My University, 2025)
This study analyzes rural internal migration towards Baku, the capital city of the republic of Azerbaijan, as a structural socio-economic challenge. By identifying the key economic, institutional, and social push and pull factors driving migration decisions, this study aims to find out the «pull» and «push» factors of the internal migration from the regions of Azerbaijan to the capital city of Baku. The study also explores reasons for the absence of significant gap reduction in the past state-led regional development programs, as well as the proposed policy frameworks with practical, evidence-based measures that can address issues of the underlying cause of chronic urban-centered migration. This study also seeks to explain the underperformance of previous state-led regional development programmes in addressing territorial inequalities, by adopting a mixed-methods approach that combines the use of surveys with expert interviews and secondary statistical sources that should help to develop policy measures that will address the root causes of continuing urban migration. The results reveal that internal migration in Azerbaijan is motivated to some degree by economic underdevelopment, strong centralization of educational, healthcare, cultural, and administrative resources in Baku and weak institutional autonomy of the local governments. Structural disparities remain despite several state-led regional development projects, thus migration is a reasonable household strategy. The study finds that counteracting internal migration requires a sequenced policy response prioritising reform of local governance, local strategic investments via public–private partnerships and the decentralisation of educational infrastructure.
Keywords: internal migration; regional development; centralization; Azerbaijan; public-private partnership; education policy; local governance; post-Soviet economies